Early cochlear implantation supports narrative skills of children with prelingual single-sided deafness - Arras, Tine; Boudewyns, An; Dhooge, Ingeborg; Zarowski, Andrzej; Philips, Birgit; Desloovere, Christian; Wouters, Jan; van Wieringen, Astrid (Scientific reports, 2023)
Prelingual single-sided deafness (SSD) not only affects children’s hearing skills, but can also lead to speech-language delays and academic underachievement. Early cochlear implantation leads to improved spatial hearing, but the impact on language development is less studied. In our longitudinal study, we assessed the language skills of young children with SSD and a cochlear implant (CI). In particular, we investigated their narrative skills in comparison to two control groups: children with SSD without a CI, and children with bilateral normal hearing. We found that children with SSD and a CI performed in line with their normal-hearing peers with regard to narrative and verbal short-term memory skills. Children with SSD without a CI had worse narrative (group difference = − 0.67, p = 0.02) and verbal short-term memory (group difference = − 0.68, p = 0.03) scores than the implanted group. Verbal short-term memory scores and grammar scores each correlated positively with narrative scores across all groups. Early grammar scores (at 2–3 years of age) could partially predict later narrative scores (at 4–6 years of age). These results show that young children with prelingual SSD can benefit from early cochlear implantation to achieve age-appropriate language skills. They support the provision of a CI to children with prelingual SSD.